UPGRADING WAWASAN BAGI KADER KELILING ANTI HIV AIDS ERA PANDEMI (WADER LAHAP) - Astuti, Dhesi Ari; Kurniati, Nurul; Ardina, Mega (Universitas Muhammadiyah Tangerang, 2022)
Based on the results of HIV/AIDS surveillance in the period from 2004 to 2019, the total number of people living with HIV/AIDS is 1247 cases. This number includes new cases of HIV/AIDS in 2019, as many as 128 cases of HIV and 33 cases of AIDS. The prevalence of HIV/AIDS in 2019 from 128 is divided by the general population target, which is 0.012%, the prevalence status is Concentrated Epidemic. The importance of HIV/AIDS screening efforts as a solution for the community and the importance of education for families is one of the top priorities. Cadres are one of the extensions of health workers in providing education to the community. In this activity, an understanding upgrade for regional cadres was carried out with the atmosphere of the Covid-19 pandemic. There is an increase in knowledge for cadres about HIV AIDS.